Pengaruh Strategi Segmenting, Targeting, Dan Positioning Terhadap Keputusan Pembelian Produk Di Warkop Kamandanu Tulungagung - Ryan Suhandito; Muhammad Alhada Fuadilah Habib (Universitas 45 Surabaya, 2024)
The increasingly rapid development of the culinary or food and beverage (F&B) world requires business actors to prepare clear and structured marketing strategies. One marketing strategy that can be carried out by business actors is the STP (Segmenting, Targeting and Positioning) marketing strategy so that the products that will be marketed to consumers will be more focused and structured. Therefore, this research raises the issue of segmenting, targeting and positioning strategies on purchasing decisions. The purpose of this research is to (1) examine the influence of segmenting, targeting and positioning variables on product purchasing decisions, (2) examine the influence of segmenting variables on product purchasing decisions, (3) examine the influence of targeting variables on product purchasing decisions, (4) examine the influence of positioning variables on product purchasing decisions. This research uses a quantitative approach with an associative type of research. The sampling method is non-probability sampling using an accidental sampling technique and a sample size of 100 respondents. The types of data used are primary and secondary data. Questionnaire data were analyzed using SPSS Version 29 by testing validity, reliability, multicollinearity, multiple linear regression, coefficient of determination, hypothesis testing (F test and T test), and classical assumption tests (normality, heteroscedasticity and autocorrelation tests). The results of this research show that, (1) Segmenting, targeting and positioning strategies simultaneously have a positive and significant effect on purchasing decisions, (2) Partial segmenting strategies have a positive and significant effect on purchasing decisions, (3) Partial targeting strategies have a positive effect and significant on purchasing decisions, (4) Positioning strategy partially has a positive and significant effect on purchasing decisions.